Аналіз технологічних процесів для опрацювання результатів наземного лазерного сканування (на прикладі пам'ятника С.Бандері) - Савчук, Наталія Вікторівна; Savchuk, Nataliia Viktorivna (Національний університет "Львівська політехніка", 2024)
У бакалаврській кваліфікаційній роботі розглянуто застосування технології наземного лазерного сканування (НЛС) для цифрової фіксації об’єктів культурної спадщини, зокрема пам’ятника Степану Бандері у місті Львів. Основну увагу приділено порівняльному аналізу функціоналу трьох програмних середовищ: Trimble RealWorks, CloudCompare та QT Modeler, які використовувалися для опрацювання хмар точок, отриманих під час сканування [Shanoer & Abed, 2018; CloudCompareWiki, 2024]. У роботі наведено теоретичні основи лазерного сканування, схарактеризовано технічні параметри сканера Trimble TX6, описано методику польових робіт, включаючи підготовку мішеней та розміщення сканувальних станцій [Trimble TX6 – ТОВ “КМС”, 2023]. Виконано повне опрацювання отриманих даних: реєстрацію, очищення від артефактів за допомогою плагіну Virtual Broom, обчислення щільності, геометричних характеристик та статистичних параметрів [Savchuk et al., 2024]. Хмари точок аналізувались у CloudCompare за допомогою функцій об’ємної щільності, кількості сусідів, а також площинності, лінійності та вертикальності [Suchocki, 2020]. У QT Modeler оцінювались функції Number of Points та Density у межах регулярної сітки, що дозволило здійснити кількісну оцінку густоти просторових даних [Applied Imagery, 2024]. Практична цінність роботи полягає у створенні алгоритму цифрової фіксації складних архітектурних форм у контексті культурної спадщини. Результати можуть бути використані у сферах архітектурної реставрації, 3D-моделювання, інженерної геодезії, а також інтегровані в BIM/ГІС-середовища [Shanbari et al., 2016]. Робота також демонструє важливість цифрового збереження об’єктів в умовах збройного конфлікту, зокрема у контексті руйнувань культурної спадщини [Втрати історичної та культурної спадщини України, 2022].

This bachelor's thesis explores the application of terrestrial laser scanning (TLS) technology for the digital documentation of cultural heritage objects, specifically the monument to Stepan Bandera in the city of Lviv. Special attention is given to the comparative analysis of three software platforms: Trimble RealWorks, CloudCompare, and QT Modeler, which were used for processing point clouds obtained through scanning (Shanoer & Abed, 2018; CloudCompareWiki, 2024). The work outlines the theoretical foundations of laser scanning, describes the technical specifications of the Trimble TX6 scanner, and provides a detailed methodology for field operations, including the preparation and positioning of scanning targets (Trimble TX6 – KMS, 2023). A full data processing workflow is implemented, including registration, artifact removal using the Virtual Broom plugin, density calculation, geometric feature extraction, and statistical analysis (Savchuk et al., 2024). Point clouds were analyzed in CloudCompare using functions such as volumetric density, number of neighbors, and geometric features including planarity, linearity, and verticality (Suchocki, 2020). In QT Modeler, the Number of Points and Density functions were evaluated within a regular grid, allowing a quantitative assessment of spatial data density (Applied Imagery, 2024). The practical significance of this work lies in developing a digital workflow for documenting complex architectural forms within a cultural heritage context. The results can be implemented in architectural restoration, 3D modeling, engineering surveying, and integrated into BIM/GIS environments (Shanbari et al., 2016). Moreover, the research highlights the critical importance of digital heritage preservation amid armed conflict, particularly in the context of war-related destruction of historical monuments (Losses of Ukraine’s Historical and Cultural Heritage, 2022).
Analysis of technological processes for processing the results of ground laser scanning: a case study of the monument to S. Bandera
Keywords: 6.193.00.00; наземне лазерне сканування; Trimble TX6; CloudCompare; QT Modeler; хмара точок; геометричний аналіз; цифрова фіксація; архітектурна спадщина; 3D-моделювання; геоінформаційні системи. Літературні джерела 1. Savchuk; N.; Babiy; L.; Bakula; K.; & Pilarska-Mazurek; M. (2024). Comparative analysis of point clouds obtained from UAV for complex engineering constructions. У International conference of young professionals «Geoterrace-2024» (с. 1–5). European Association of Geoscientists & Engineers. https://doi.org/10.3997/2214-4609.2024510011 2. Shanbari H A; Blinn N M; Issa R R (2016). Laser scanning technology and BIM in construction management education; ITcon Vol. 21; Special issue 9th AiC BIM Academic Symposium & Job Task Analysis Review Conference; pg. 204-217; https://www.itcon.org/2016/14 3. Shanoer; M. M.; & Abed; F. M. (2018). Evaluate 3D laser point clouds registration for cultural heritage documentation. The Egyptian Journal of Remote Sensing and Space Science; 21(3); 295–304. https://doi.org/10.1016/j.ejrs.2017.11.007 4. Suchocki; C. (2020). Comparison of time-of-flight and phase-shift TLS intensity data for the diagnostics measurements of buildings. Materials; 13(2); 353. https://doi.org/10.3390/ma13020353 5. Втрати історичної та культурної спадщини України під час війни. (2022; 31 березня). Район.Історія. https://history.rayon.in.ua/news/501852-vtrati-istorichnoi-ta-kulturnoi-spadshchini-ukraini-pid-chas viyni#group=redactor&photo=11 6. CloudCompareWiki. CloudCompare - Open Source project. https://www.cloudcompare.org/doc/wiki/index.php/Main_Page 7. Tutorials - applied imagery. Applied Imagery. https://appliedimagery.com/tutorials/ 8. Trimble TX6 - ТОВ “КМС”. ТОВ “КМС” -. https://kmcgeo.com/ua/lazernye-skanery/3d_tx6/; terrestrial laser scanning; Trimble TX6; CloudCompare; QT Modeler; point cloud; geometric analysis; digital documentation; cultural heritage; 3D modeling; geographic information systems